2020
DOI: 10.1016/j.ccell.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Synaptic Transfer of Tumor Antigens among Dendritic Cells

Abstract: Highlights d Myeloid cells retain tumor-derived antigens in intracellular vesicles d Dynamic synapses facilitate membrane and vesicular exchange between myeloid cells d Migratory DC pass vesicular tumor antigen to resident DC at points of contact d Migratory versus resident cDC1 exhibit differential T cell priming characteristics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(127 citation statements)
references
References 47 publications
9
118
0
Order By: Relevance
“…During an effective antitumor immune response, APCs uptake and present tumor antigens to T cells, leading to T cell activation for tumor destruction 45 . In an established tumor microenvironment, majority of the infiltrating T cells are dysfunctional 46 .…”
Section: Discussionmentioning
confidence: 99%
“…During an effective antitumor immune response, APCs uptake and present tumor antigens to T cells, leading to T cell activation for tumor destruction 45 . In an established tumor microenvironment, majority of the infiltrating T cells are dysfunctional 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Although recent findings have indicated that there is a synapse between various DCs to share tumor antigens ( 107 ), human DCs can be divided into plasmacytoid DC (pDC), conventional DC (cDC), and monocyte-derived DCs (MoDC) subsets. The cDCs can also be subdivided into cDC1 and cDC2 subgroups ( 108 – 110 ).…”
Section: Dcs In the Tumor Microenvironment And Dc-based Vaccine Develmentioning
confidence: 99%
“…DCs are the most efficient antigen-presenting cells that take up, process and present antigens to T cells, which contribute to the initiation and progression of immune responses 20 . Early studies reported that DC-derived EVs expressed high levels of functional major histocompatibility complex (MHC) class I (MHC-I) and class II (MHC-II), MHC-peptide complexes, T cell costimulatory molecules, and tumor antigens 21 - 23 . In addition, it was shown that EVs derived from LPS-induced DCs carried multiple classes of RNAs, including miRNAs, small nucleolar RNAs, Y-RNAs, tRNAs, and small nuclear RNAs 24 , which may have roles in balancing T helper 1(Th1)/Th2 responses 25 .…”
Section: Characteristics and Functions Of Evs From Cells Associated Wmentioning
confidence: 99%